Economic Complexity and the Potential for Green Growth in South Africa - Wewege, Sarah Joy (School of Economics, 2021)
South Africa's reintegration into the global economy post-1994 has not produced the expected levels of industrialisation and growth-enhancing structural transformation that has traditionally been achieved by developed countries in the past. South Africa faces the triple challenge of poverty, inequality and unemployment and needs structural growth that is inclusive and sustainable. However, trying to emulate the traditional structural transformative growth paths that developed countries have followed previously, will prove unsuccessful due to changes in the global economy. This paper, therefore, argues that an alternate growth path is needed, especially given that global warming and the effects of climate change act as a threat multiplier to economic growth and development. Furthermore, the world economy is shifting away from fossil fuels and resource depletion towards greener technologies and products. South Africa needs to adopt a growth path that accounts for the current climate and global context to ensure sustainable and inclusive growth for future competitiveness. This paper, using the Economic Complexity Methodology, identifies green industries that South Africa is best positioned to develop and grow given the existing knowledge and capabilities within the economy. A case study is conducted on the wind-power industry which proves to be a promising option given South Africa's current economic climate and the potential for employment creation. This paper aims to highlight the opportunities for the development of green industries in South Africa and the limitations that hinder this potential.